Improving coffee soil health using compost made from sugarcane leaves, coffee pulp, and Gliricidia sp. - Afifatul Khoirunnisak; Sugeng Prijono; Lenny Sri Nopriani; Budi Prasetya; Atiqah Aulia Hanuf (Universitas Sebelas Maret, 2025)
Agricultural waste management remains a critical environmental concern, necessitating sustainable approaches to transform organic residues into valuable resources. Among these, composting offers an effective solution by converting biomass into nutrient-rich soil amendments and reducing the burden of waste disposal. This study aims to investigate the potential of combined agricultural waste composting for producing high-quality compost and enhancing soil properties in a coffee plantation. Eight composting treatments and three replications were formulated: P1: Saccharum officinarum leaves (100%), P2: Coffee pulp (100%), P3: Gliricidia sp. leaves (100%), P4: Saccharum officinarum leaves (50%) + Coffee pulp (25%) + Gliricidia sp. leaves (25%), P5: Coffee pulp (50%) + Saccharum officinarum leaves (25%) + Gliricidia sp. leaves (25%), P6: Gliricidia sp. leaves (50%) + Coffee pulp (25%) + Saccharum officinarum leaves (25%), P7: Coffee pulp (50%) + Saccharum officinarum leaves (50%), and P8: Coffee pulp (50%) + Gliricidia sp. leaves (50%). The findings indicated that the compost mixtures containing Gliricidia sp. leaves and coffee pulp yielded a C:N ratio of less than 25, signifying that the compost was mature. The application of compost resulted in an overall increase in soil pH, organic carbon, and total nitrogen, while also ameliorating soil structure through reduced bulk density and enhanced porosity, particularly at a depth of 30–60 cm. These results provide valuable insights for farmers and agricultural policymakers in developing sustainable waste management strategies that effectively address agricultural waste disposal challenges while improving soil fertility and promoting more environmentally friendly coffee production systems.